2011
DOI: 10.1016/j.ceramint.2011.01.041
|View full text |Cite
|
Sign up to set email alerts
|

The effect of precursor composition and sintering additives on the formation of β-sialon from Al, Si and Al2O3 powders

Abstract: This version is available at https://strathprints.strath.ac.uk/30842/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…1. Ewing and Yang [17] reported that 15R polytype Sialon appeared when whiskers could be formed at different temperatures, and the increase of the sintering temperature resulted in the higher yield and larger diameter of the SiC whisker. The growth mechanism of the SiC whiskers followed VS (vapor-solid) or VLS (vapor-liquid-solid) model [19][20][21].…”
Section: Resultsmentioning
confidence: 98%
“…1. Ewing and Yang [17] reported that 15R polytype Sialon appeared when whiskers could be formed at different temperatures, and the increase of the sintering temperature resulted in the higher yield and larger diameter of the SiC whisker. The growth mechanism of the SiC whiskers followed VS (vapor-solid) or VLS (vapor-liquid-solid) model [19][20][21].…”
Section: Resultsmentioning
confidence: 98%
“…[11][12][13][14] They have the same liquid-phase sintering mechanism: The sintering additives react with SiO 2 on the surface of the Si 3 N 4 particles to generate a low-eutectic-point liquid phase that wets the solid phase and thus accelerates the particle rearrangement and solid-phase dissolution-precipitation and promotes the densification of the Sialon ceramics. 15,16 However, under the action of the above sintering additives, the densification and toughening of Sialon ceramics are synchronized, and the hierarchical control cannot be realized. In this regard, how to realize the phased control of sintering aids in the densification and toughening of Sialon ceramics is the current research difficulty.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the universally applied sintering additives are mainly single inorganic additives (such as MgO, Al 2 O 3 , and Y 2 O 3 ) 8–10 or composite sintering additives (such as Al 2 O 3 –Y 2 O 3 and Re 2 O 3 –MgO) 11–14 . They have the same liquid‐phase sintering mechanism: The sintering additives react with SiO 2 on the surface of the Si 3 N 4 particles to generate a low‐eutectic‐point liquid phase that wets the solid phase and thus accelerates the particle rearrangement and solid‐phase dissolution–precipitation and promotes the densification of the Sialon ceramics 15,16 . However, under the action of the above sintering additives, the densification and toughening of Sialon ceramics are synchronized, and the hierarchical control cannot be realized.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve performance, it is preferred that the introduced metal can further transform into 15R-Sialon. Due to the difficulty of nitridation of Si and Al to Sialon, 23 the direct addition of Al and Si may not be a good choice. Relevant studies have found that Si 3 N 4 will react with Al to Si and AlN, 24,25 which can provide solid nitrogen source and liquid metal phase for the synthesis of 15R-Sialon.…”
Section: Introductionmentioning
confidence: 99%